IbM PRODUK HERBAL DI UKM LAWU HERBAL DAN UKM PONDOK DAUN HERBAL - Aulia Qonita; Nur Her Riyadi Parnanto (Asian Journal of Innovation and Entrepreneurship, 2016)
This activity is carried out in SMEs Lawu Herbal UKM in Mawar Street  No 03. Dimoro RT 02 RW 10 Karanganyar village, District of Karanganyar and SMEs Pondok Daun in Rajawali Street No. 8, Ngebrak RT 01 / XI, Gentan, Baki, Sukoharjo. This activity aims to provide solutions  of  problems which is  faced by SMEs. The problem faced by SMEs Lawu Herbal is a simple plastic packaging is still using ordinary sealer system; marketing still limited and not use the media website. The problem is faced by SMEs Pondok Daun Herbal is the unavailability of neat book keeping. This activities carried out by the introduction of vacuum sealer tools, marketing training through the website and the training of financial accounting and management improvements.Results from service activities are 1) the packaging of products in SMEs Lawu Herbal become better, more durable and fresh, 2) SMEs Lawu Herbal own website so marketing becomes more widespread, 3) Both SMEs already have a simple bookkeeping, 4) Mentoring in both SMEs have been implemented, and 5) the assistance of both SMEs business development is gotten  from the Ministry of Cooperation of the Republic of Indonesia.